Ekstradisi Dalam Meningkatkan Kerja Sama Penegakkan Hukum - Atmasasmita, Romli (UI Scholars Hub, 2007)
Law enforcement cooperation in international relations is crucial to determine on whether or not national law enforcement to transnational crimes is succeed. The oldest cooperation is extradition followed by other cooperation such as mutual legal assistance treaty, transfer of sentenced person, transfer of criminal proceedings, joint investigation and handing over. This article tries to examine the reasons why those kinds of agreement are needed in law enforcement cooperation. It specifically discuss on Indonesia’s experience in concluding those agreement with its neighboring states within ASEAN.